Monolingualism of US Poetry: Language Barriers for Poetry in Spanish - Benito del Pliego (Studies in 20th & 21st Century Literature, 2020)
The growing acceptance of US Latino voices in the US literary canon is also bringing to the attention of the critics the limitations of this inclusiveness. US Latino or Hispanic literatures are a far more complex phenomenon than commonly portrayed. This complexity is interlaced with the even wider frame of the multi-ethnic, multi-lingual literary realities of the US, a country where languages other than English have been historically relegated to a secondary role by concerted policies of cultural domination. In such context, it is relevant to explores the social origins and the implications of the systematical bias against the literary productions of Latino/a poets whose main language is Spanish. Many of these poets also have very important transnational connections. The poetry of José Kozer, Cecilia Vicuña, and Lorenzo García Vega illustrate the challenges that arise when attempting to incorporate multicultural, multilingual, and transnational authors into a critical literary frame that still relies on sanctioned national parameters.
Keywords: US Latinx poets; US literature in Spanish; US hispanophone poets; Exile; Transnational poetry; José Kozer; Cecilia Vicuña; Lorenzo García Vega